Teaching performance in the academic performance of students of the professional school of civil engineering, Universidad Ricardo Palma 2022 - Loyola Santos, Arturo Andreí (2024)
This study aims to determine if teaching performance is related to the academic performance of students in the subject Construction II of the professional school of civil engineering, Ricardo Palma University. The study corresponds to the type of basic research, with a quantitative approach, at the explanatory level. causal, with a non-experimental design, the sample was made up of 100 students. The validation of the information gathering instrument was submitted to the criteria of specialists, which was a questionnaire and a questionnaire for the academic test. For reliability, we used the Cronbach coefficient, which obtained a coefficient of 0.891, and 0.875, presenting a high level of reliability. The application of the >Spearman test resulted in a value of 7.78 for the general hypothesis; The p value or Sig. Asymptotic (bilateral) was 0.000, which is less than the 0.05 level of significance and it is concluded that teaching performance is significantly related to the academic performance of students of the subject Construction II of the professional school of civil engineering of the URP.